Exploring entrepreneurial orientation – Performance relationships in the banking sector - Dantsoho, Mohammed Aliyu; Umar, Salisu; Aminu, Mohammed Ibrahim; Abdullahi, Nasiru; Adamu, Abubakar Ado (2020)
Over the past three decades, the nature and various impacts of the entrepreneurial orientation (EO) within small and medium businesses have been discussed among scholars and practising managers. However, less effort has been made to investigate the impacts of EO within established firms such as the banking sector. This literature gap can limit the application of the most published findings on EO –performance relationships across firms and industries. The aim of this research was to examine how EO manifest in the Nigerian banking sector in relations to bank performance. Purposive sampling was used to collect data from the bank managers, 315 participants were used for the final analysis with the aid of SmartPLS 3.2.8 statistical software. The result shows that Proactiveness, Innovativeness and Competitive aggressiveness are significantly related to the performance of banks in Nigeria, whereas Risk-taking and Autonomy dimensions were insignificant. Individually, the result indicates that proactiveness is the most important EO dimension in the Nigeria banking sector, then followed by innovativeness and competitive aggressiveness. Reasons for this finding could be due to the nature of the industry in terms of regulations, customer sophistication and competitive intensity. Our findings hence, confirms recent assertions that EO dimensions are independent of each other, they may occur in different combinations depending on the context which EO is applied. That is the most suitable EO conceptualisation can include features that are deemed 'desirable or essential’ (Gupta & Dutta, 2018: 167), to performance in a given culture and specific industries (Wales, 2020). In light of these findings, this study recommends bank’s managers to pay attention to EO construct in terms of proactiveness, innovativeness and competitive aggressiveness to improve performance. Thereby, addressing the issues of competitive intensity, customer sophistication and changing regulation. This study brings new insights to the ongoing discussions on EO – performance relationships.